2000
DOI: 10.7773/cm.v26i1.571
|View full text |Cite
|
Sign up to set email alerts
|

Oral challenge of postlarvae of Litopenaeus Vannamei through bioencapsulation of Vibrio parahaemolyticus in Artemia franciscana

Abstract: Recibido en enero de 1999; aceptado en julio de 1999 RESUMEN Aunque la vibriosis haya causado pérdidas financieras muy grandes en la camaronicultura, todavía no existe un modelo para estudiar esta enfermedad; por tanto, el objetivo de este estudio fue desarrollar dicho modelo. Dos tratamientos fueron aplicados al camarón blanco Litopenaeus vannamei. Los camarones se alimentaron con Vibrio parahaemolyticus bioencapsulado en nauplios de Artemia franciscana y los controles se alimentaron con nauplios estériles. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The bioencapsulation of bacteria results presented here and elsewhere (Gomez-Gil et al 1998, Makridis et al 2000, Roque et al 2000, Verschuere et al 2000 suggest that Artemia franciscana nauplii have a maximum capacity for bioencapsulation (ingestion) of bacterial cells ranging from 10 2 to 10 4 CFU nauplius -1 , independent of the bacterial density to which they are exposed (10 6 to 10 8 CFU ml -1 ) but dependent on the bacterial strain employed. The density of bacteria Table 2.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The bioencapsulation of bacteria results presented here and elsewhere (Gomez-Gil et al 1998, Makridis et al 2000, Roque et al 2000, Verschuere et al 2000 suggest that Artemia franciscana nauplii have a maximum capacity for bioencapsulation (ingestion) of bacterial cells ranging from 10 2 to 10 4 CFU nauplius -1 , independent of the bacterial density to which they are exposed (10 6 to 10 8 CFU ml -1 ) but dependent on the bacterial strain employed. The density of bacteria Table 2.…”
Section: Discussionmentioning
confidence: 87%
“…nauplii for delivery to aquatic animal larvae (Mohney et al 1990, Chair et al 1991, Touraki et al 1995, Roque et al 1998), a process known as bioencapsulation. Bacteria have been similarly incorporated to evaluate their pathogenic, probiotic, or therapeutic potential (Rico-Mora & Voltolina 1995, Gomez-Gil et al 1998, Roque et al 2000. For example, bioencapsulated fish pathogenic bacteria have been used to investigate the infection route in turbot larvae (Chair et al 1994) and to vaccinate fish fry (Campbell et al 1993) and juvenile carp (Joosten et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Vários trabalhos já foram publicados evidenciando-se a importância da artêmia na alimentação dos organismos aquáticos (Ovie e Adepoju, 1996;Cabanilas et al, 2001;Luz e Zanibone, 2001). No entanto, ênfase deverá ser dada ao trabalho de Roque et al (2000), ao verificarem que a artêmia quando administrada às pós-larvas de L. vannamei, durante 7 dias de cultivo, foi responsável por níveis de sobrevivência melhores do que outras fontes de alimentação. Resultados equivalentes foram encontrados por Valenzuela et al (1999), porém, os melhores resultados foram obtidos utilizando-se misis de L. vannamei.…”
Section: Resultsunclassified
“…Standard Error (SE) results also showed 2.15, 3.2 and 3.20 in experimental, duplicate and triplicate found significant. Many scientists (Makridis et al, 2000;Roque et al ., 2000) suggested that A. franciscana nauplii have a maximum capacity for bioencapsulation (ingestion) of bacterial cells ranging from 10 2 to 10 4 CFU nauplius-1, independent of the bacterial density to which they are exposed (10 6 to 10 8 CFU ml-1) but dependent on the bacterial strain employed.…”
Section: Level Of Pathogenicity Between Isolatesmentioning
confidence: 99%